Carnavalisation et travail des stéréotypes dans La Guerre, yes sir! (1968) de Roch Carrier - Kwaterko, Józef (Romanica Silesiana, 2021)
Carrier’s novel was published in the same year as Nègres blancs d’Amérique by Pierre Vallières and it relies on the same dialectics between the colonizer and the colonized that was prevalent in Québécois narrative prose in the 1960s. While being grounded in this cultural context, Carrier transforms this dialectic by setting his narrative in a rural environment and against the background of World War II (the visitation of a fallen French-Canadian soldier whose remains are escorted to his native village by English-Canadian comrades). Such aesthetic reworking complexifies the ideological message of Carrier’s novel. I will study the interplay between national ideology and Carrier’s narratives strategies and particularly on the clash between ethnic stereotypes and the « carnavalesque » and the grotesque.